2002
DOI: 10.4049/jimmunol.168.9.4796
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Decreases in Blood Plasmacytoid Dendritic Cell Number and Function Despite Effective Highly Active Antiretroviral Therapy and Increased Blood Myeloid Dendritic Cells in HIV-Infected Individuals

Abstract: Dendritic cells (DC) have an instrumental role in the activation and function of both innate and adaptive immune responses. In humans, at least two distinct DC subsets have been characterized based on phenotypic markers: the myeloid DC (MDC) and the plasmacytoid DC (PDC). Both subsets are critical producers of cytokines (IL-12 for MDC and type I/II IFNs for PDC) and are functionally different. We show in this study that HIV+ individuals have a significant decrease in the number of the Lin−HLA-DR+CD123+ and BDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
237
9
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(281 citation statements)
references
References 32 publications
27
237
9
8
Order By: Relevance
“…3A) stimulated with the TLR7 and TLR7/8 agonists. A reduced frequency of pDC in HIV + individuals which is consistent with previously published reports (6,26,27,35), may be responsible for the lower concentrations of IFN-α detected in HIV-1 infected individuals. To discriminate between qualitative and quantitative abnormalities in pDC function, we measured the intracellular expression of IFN-α at the single cell level using a broad range of synthetic and natural TLR ligands.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3A) stimulated with the TLR7 and TLR7/8 agonists. A reduced frequency of pDC in HIV + individuals which is consistent with previously published reports (6,26,27,35), may be responsible for the lower concentrations of IFN-α detected in HIV-1 infected individuals. To discriminate between qualitative and quantitative abnormalities in pDC function, we measured the intracellular expression of IFN-α at the single cell level using a broad range of synthetic and natural TLR ligands.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown impaired IFN-α secretion by pDC and defective monocyte maturation post-TLR9 (CpG ODN) stimulation in HIV-1-infected individuals (26,35,44). To expand on these studies we demonstrated a dysregulation in total IFN-α (pg/ml) secretion in PBMC cultures from HIV + individuals (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, pDCs express CD123, BDCA-2 and BDCA-4 antigens. 7,8 They also express different patterns of pathogen recognition receptors and respond to different microbial antigens. The main function of pDCs appears to be the production of a large amount of type I interferons (IFNs) in response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue in the field of DC-HIV biology is that data derived from studies using particular subtypes of DC (e.g., Langerhans cells vs monocyte-derived DC, immature vs mature DC, myeloid vs plasmacytoid DC) have clearly demonstrated disparate results. Regarding the immunologic function of HIV-infected DC or of DC isolated from HIV-infected individuals, existing literature on this topic is also varied (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Some have claimed significant APC defects and others none.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%